1996
DOI: 10.1080/00288233.1996.9513196
|View full text |Cite
|
Sign up to set email alerts
|

Faecal egg count and food intake comparisons of Romney single‐trait selection and control lines

Abstract: Two sets of correlated responses were studied in five Romney selection lines and their controls. The lines were from one experiment selecting for yearling body weight or yearling fleece weight since 1967, from a second experiment selecting for weaning weight or yearling fleece weight since 1973, and from a third experiment selecting for yearling body weight since 1973. Overall, the five selection lines were evaluated whilst being run together with controls at a single site. The responses were faecal egg count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…The lower fleece weights in lambs and ewes in the low FEC selection line than in the high line were consistent with our preliminary results from the same flock of Perendales (Morris et al 1997b), and with the results from the equivalent Romney selection experiment in New Zealand where animals from the two FEC lines also grazed together (Morris et al 1997a). Earlier New Zealand results (all reviewed by Morris et al 2000) from Romney fleece-weight selection lines at Massey University (Howse et al 1992;Williamson et al 1995) and at Tokanui Station (Morris et al 1996) were positive in sign (lower fleece weights associated with low FEC). Paternal half-sib data for FEC and wool growth (from midside patches over the parasite challenge period) at an AgResearch property (Woodlands) also showed large positive genetic correlations, although nearzero phenotypic correlations (McEwan et al 1992).…”
Section: Correlated Responsessupporting
confidence: 81%
See 1 more Smart Citation
“…The lower fleece weights in lambs and ewes in the low FEC selection line than in the high line were consistent with our preliminary results from the same flock of Perendales (Morris et al 1997b), and with the results from the equivalent Romney selection experiment in New Zealand where animals from the two FEC lines also grazed together (Morris et al 1997a). Earlier New Zealand results (all reviewed by Morris et al 2000) from Romney fleece-weight selection lines at Massey University (Howse et al 1992;Williamson et al 1995) and at Tokanui Station (Morris et al 1996) were positive in sign (lower fleece weights associated with low FEC). Paternal half-sib data for FEC and wool growth (from midside patches over the parasite challenge period) at an AgResearch property (Woodlands) also showed large positive genetic correlations, although nearzero phenotypic correlations (McEwan et al 1992).…”
Section: Correlated Responsessupporting
confidence: 81%
“…An effect with the same sign was also observed for winter weight, yearling weight, 18-month weight, and adult ewe weight (Tables 3 and 4). Earlier results from New Zealand Romney lines selected for low FEC (Morris et al 1997a;2000) or lines selected for high weight (Morris et al 1996) showed a positive relationship (unfavourable sign) between FEC and New Zealand Journal of Agricultural Research, 2005, Vol. 48 weight on some occasions; whenever the difference or the correlated response between the selection lines was significant, the sign was always positive.…”
Section: Correlated Responsesmentioning
confidence: 99%
“…This was assessed on lines of sheep selected either for wool production or for meat production where faecal egg excretion or worm burdens were significantly higher as compared to values from non selected animals [36,50,77]. In addition, on a study measuring host resistance to internal parasites on lines of sheep selected for different traits of production, positive correlations calculated between lines were found between egg excretion and liveweight or wool growth [49].…”
Section: Identification Of Less Resistant/resilient Animals Related Tmentioning
confidence: 99%
“…As a result, FEC has been widely used to estimate genetic variation in resistance to nematode infestation in sheep Morris et al, 1996;Cloete et al, 2000;Khusro et al, 2004;Yadav et al, 2006;Cloete et al, 2007;Snyman, 2007) and goats (Mandonnet et al, 2001;Olayemi et al, 2001;Chauhan et al, 2003;Mandal & Sharma, 2008). Several authors have reviewed genetic parameters for resistance to nematodes in sheep (Safari et al, 2005;Morris, 2011).…”
Section: Introductionmentioning
confidence: 99%